Pranlukast hydrate in the treatment of pediatric bronchial asthma - Yoshihara S (Dove Medical Press, 2013)
Shigemi Yoshihara Department of Pediatrics, Dokkyo Medical University, Tochigi, Japan Abstract: Pranlukast hydrate is a potent, selective, orally active, cysteinyl leukotriene antagonist that binds at the type 1 receptor. It is used as a 10% dry syrup to treat asthma and allergic rhinitis in pediatric patients. In a 4-week, dose-finding study, a dose-dependent improvement in lung function was observed in pediatric patients with asthma at an optimal dose of 5.1–10 mg/kg/day. In a comparative, randomized, double-blind, 4-week multicenter trial, pranlukast dry syrup 7 mg/kg/day achieved significantly better final overall improvement (71.4%) versus oxatomide 1 mg/kg/day (37.2%) in pediatric patients older than one year with asthma. In two 12-week, open-label trials and in a long-term open-label trial of treatment for up to 24 months, pranlukast dry syrup improved asthma control over baseline values. In a prospective post-marketing surveillance study and a long-term follow-up study, the safety and efficacy of pranlukast dry syrup was confirmed in infants younger than one year with bronchial asthma. In a 4-week, open-label trial, pranlukast dry syrup improved overall health-related quality of life and physical and emotional domain scores over baseline in pediatric patients with asthma. In a randomized, multicenter, double-blind, placebo-controlled, two-period crossover trial, pranlukast dry syrup significantly inhibited exercise-induced bronchospasm in children with asthma compared with placebo. In a modified Childhood Asthma Control Test, pranlukast dry syrup was significantly more effective in controlling asthma in patients younger than 4 years with the common cold. These findings show that pranlukast is useful and beneficial for treating pediatric patients with bronchial asthma. Keywords: pranlukast, leukotriene receptor antagonist, pediatric asthma